2020
DOI: 10.21873/invivo.11946
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: The Potential Role of Copper and N-acetylcysteine (NAC) in a Combination of Candidate Antiviral Treatments Against SARS-CoV-2

Abstract: Background: On March 11, 2020, the World Health Organization (WHO) declared the outbreak of coronavirus disease (COVID-19) a pandemic. Since then, thousands of people have suffered and died, making the need for a treatment of severe acute respiratory syndrome-related coronavirus-2 (SARS-CoV-2) more crucial than ever. Materials and Methods: The authors carried out a search in PubMed, Clinical Trials.gov and New England Journal of Medicine (NEJM) for COVID-19 to provide information on the most promising treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 91 publications
(166 reference statements)
2
96
0
4
Order By: Relevance
“…A potential role of NAC and copper in combination with candidate antiviral treatments against SARS-CoV-2, such as remdesivir, has been hypothesized based on a systematic literature search. 71 Clearly, the potential anti-COVID-19 mechanisms and properties of this thiol have to be substantiated in controlled clinical trials, some of which are now in progress. 12,72…”
Section: Discussionmentioning
confidence: 99%
“…A potential role of NAC and copper in combination with candidate antiviral treatments against SARS-CoV-2, such as remdesivir, has been hypothesized based on a systematic literature search. 71 Clearly, the potential anti-COVID-19 mechanisms and properties of this thiol have to be substantiated in controlled clinical trials, some of which are now in progress. 12,72…”
Section: Discussionmentioning
confidence: 99%
“…N -Acetylcysteine is a potential therapeutic in the treatment of COVID-19 ( Andreou et al, 2020 ). It is a mucolytic drug with antioxidant activity that is used in respiratory diseases ( Mokhtari et al, 2017 ) and skin diseases ( Adil et al, 2018 ), as well as an antidote in acetaminophen overdose ( Mokhtari et al, 2017 ).…”
Section: Drugs Targeting Neutrophils For Covid-19 Associated Ardsmentioning
confidence: 99%
“…In another meta-analysis study, N -acetylcysteine treatment of ARDS patients shortened their stay in the intensive care unit ( Zhang et al, 2017 ). Finally, it has also been suggested that N -acetylcysteine should be used in combination with other drugs to manage ARDS ( Guo et al, 2019 ; Andreou et al, 2020 ; Horowitz and Freeman, 2020 ). Currently, several clinical trials with N -acetylcysteine to treat COVID-19 (NCT04419025, NCT04455243, NCT04374461, etc.)…”
Section: Drugs Targeting Neutrophils For Covid-19 Associated Ardsmentioning
confidence: 99%
“…So people who are using zinc supplements regularly may be at risk of severing SARS-CoV-2 because of malabsorption of Cu from jejunum [59]. Also, high intake of copper may have some adverse effects including gastrointestinal symptoms (cramps, abdominal pain, nausea, diarrhea, and vomiting) and kidney and liver toxicity resulting to coma [58].…”
Section: Coppermentioning
confidence: 99%